Harmonization of Trading Partners Between Indonesia–Italy: Empirical Calculations of Selected Agricultural Commodities - Kurniawan A., Erwin; Zulfikar, Akbar Lufi; Wijaya, Adi; Darma, Dio Caisar (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2024)
Initially, exports were perceived as the prestige and dignity of a nation. However, in terms of terminology, the essence of export flows is complementarity between countries, where each party has advantages, competition and excess production of a particular product to offer. The orientation of this study is to examine the relationship between tobacco exports, coffee exports, and wine exports to GDP growth in Italy–Indonesia. There are key variables which are divided into two case studies including tobacco export volume, FoB on tobacco exports, coffee export volume, FoB on coffee exports, green grape export volume, CIF on green grape exports, red wine export volume, CIF on red wine exports, GDP share of agriculture in Indonesia and Italy. The fundamental difference in wine exports from the two is that Indonesia uses green grapes and for Italy it uses red wine. The method is set through a panel data regression approach and samples for the 2013–2021. The econometric results explain that tobacco exports and coffee exports have a significant effect on the GDP share of agriculture in Indonesia–Italy. Likewise, CIF on exports of green grapes and red wines which have a significant effect on the GDP share of agriculture in both nations. These findings inspire more urgent implications for the topic of agricultural commodity exports and become an integrated whole.